PENGEMBANGAN E-MODUL BERBASIS PJBL DALAM PEMBUATAN MULTIMEDIA INTERAKTIF - Dwi, Maria Ana; Salam, Urai; Warneri, Warneri (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aimed to develop PJBL-based e-modules in the interactive multimedia created in the context of developing media that can used to make learning more effective. This study uses the Research and Development (R&D) method with the ADDIE model through the stages of Analyze, Design, Develop, Implement, and Evaluate. The subjects of this study were students of the multimedia expertise program at SMK. The PJBL-based e-module development was carried by validating media experts, design and materials, measured with a Likert scale of 1-4 and calculated with the Gregory index. Obtaining measurements from media experts a validity coefficient is 0.89, from design and media experts obtained a validity coefficient of 1. So it can concluded that PJBL-based e-module media is suitable for use as material for making interactive multimedia. The results of student responsess as measured by percentages, obtained an average student interest response of 96.34%, student motivation in learning reached an average of 93.26%. The effectiveness test through the pretest and posttest involved 30 participants with a significance of less than 0.05, showed that there was a significant difference between the pretest and posttest. Based on this, it concluded that PJBL-based e-module learning media was effective in increasing learning in making interactive multimedia in multimedia expertise competencies.